2016
DOI: 10.17511/ijpr.2016.i06.09
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal effects of heavy backpacks in school children of 11-14 years of age

Abstract: Background/Objectives: High and increasing prevalence of back pain in children and adolescent is matter of concern. Prevalence varies regionally as it depends on many variables. Heavy backpack is one of the important underlying causes. Adolescent spine is in the critical stage of development in the age group of 11-14 years. This study was carried out to decide regional cutoffs of heavy relative weights of backpacks in male and female children. Methods: In a community based co-relational study 249 male and 251 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a communitybased study in Maharashtra (India) conducted in children from various schools of the age group of 11 to 14 years, the musculoskeletal problems related to use of backpacks was more in females (66.53%) as compared to that of males (55.02%). 16 Females tend to have a higher prevalence of back pain (30%) and neck pain (33.9%) compared to that of males (25.7% and 23.8%) respectively. 17 In the present study, it was observed that only 51% of students were carrying bag weight less than 10% of their body weight.…”
Section: Discussionmentioning
confidence: 97%
“…In a communitybased study in Maharashtra (India) conducted in children from various schools of the age group of 11 to 14 years, the musculoskeletal problems related to use of backpacks was more in females (66.53%) as compared to that of males (55.02%). 16 Females tend to have a higher prevalence of back pain (30%) and neck pain (33.9%) compared to that of males (25.7% and 23.8%) respectively. 17 In the present study, it was observed that only 51% of students were carrying bag weight less than 10% of their body weight.…”
Section: Discussionmentioning
confidence: 97%